Iraq’s Development Road Project: The Legitimacy of the Ambition and the Limitations of the Regional and International Geostrategic Competition: international and political journal - Yaseen, Faisal Abdulateef (The International and Political Journal, 2024)
Iraq seeks to diversify its rentier economy, enhance the momentum of development processes, and integrate its economy with the economies of regional countries by increasing and attracting local and foreign investments in infrastructure, transportation, and energy projects. The Development Road Project seeks to establish a network of railways and roads to connect southern Iraq with Turkey and Syria. Last March, the Iraqi government announced its intention to complete it in the coming years to translate these efforts into a practical reality. The Development Road Project, or what was previously known as the Dry Canal, aims to bring about qualitative transformations in the Iraqi economy and enhance Iraq's geopolitical position by transforming the country into an important player in the field of international transportation, making it a hub and link for global trade exchange and linking it to international supply chains. However, the completion of this ambitious project faces a number of challenges represented by security obstacles, financing constraints, and financial allocations, in addition to the obstacles of internal political division and fragmentation. At the regional level, the project faces competition from international and regional projects and companies in the field of transportation, commercial shipping and transit of goods, such as the North-South International Transport Corridor project, the most important parties of which are Russia and Iran, and the Economic Corridor project linking India, the Middle East and Europe (the Green Corridor), which includes many countries such as India, the Gulf States and Jordan.